Amido Ca(ii) complexes supported by Schiff base ligands for catalytic cross-dehydrogenative coupling of amines with silanes. Issue 36 (7th June 2018) - Forosenko, Natalia V.; Basalov, Ivan V.; Cherkasov, Anton V.; Fukin, Georgy K.; Shubina, Elena S.; Trifonov, Alexander A.
Abstract : Heteroleptic Ca(ii ) amides coordinated by multidentate phenolato ligands proved to be efficient catalysts for catalytic cross-dehydrogenative coupling of amines with silanes. Abstract : A series of amido Ca complexes LCa[N(SiMe3 )2 ](THF) (1–4 ) coordinated by Schiff base ligands L 1–4 were synthesized via an amine elimination reaction between proligands L 1–4 H and a bisamido complex Ca[N(SiMe3 )2 ]2 (THF)2 in good yield. Unlike Ca[N(SiMe3 )2 ]2 (THF)2, the reactions of M[N(SiMe3 )2 ]2 (THF)2 (M = Yb, Sm) with proligands L 1–4 H do not lead to the formation of the target Ln(ii ) amido complexes. The reaction of Yb[N(SiMe3 )2 ]2 (THF)2 withL 1 H is accompanied by intramolecular C–H bond activation of a quinoline ring and results in the formation of complex6 coordinated by a new trianionic [NNNNOO] ligand. The reactions of amido complexes1 and4 with PhSiH3 do not allow for preparing the related hydrides but afford homoleptic bis(phenolate) complexes5 and7 due to a ligand redistribution reaction. Amido complexes1–4 were evaluated as precatalysts for cross-dehydrogenative coupling of silanes (PhSiH3, Ph(Me)SiH2, and Ph3 SiH) and aliphatic, aromatic and cyclic amines (RNH2 and R2 NH).